REFORMS IN HIGH EDUCATION AND THEIR INFLUENCE IN ECONOMIC DEVELOPMENT OF R. MACEDONIA - Shaqiri, Jeton (Journal of process management and new technologies, 2017)
Education as an important social activity represents the basic capital of contemporary society and, as such, today is considered to be a major factor in the economic and social development of any country. The development of education during the transition period in our country has marked significant and visible changes. The importance of education in the economic and social development of each country is one of the topics around the world discussed in various aspects. Investing in education is quite remarkable, because it is an investment in knowledge, technology, science - "brain drain", a future investment and is one of the decisive factors for today’s socio-economic development with current changes and current global development.Due to education, in some countries are made great scientific discoveries and technically-technological revolutions, which have been crucial to humanity in general. In fact, education is knowledge and knowledge is the driving force behind the overall development of a society. World-renowned economists such as Adam Smith and Alfred Marshall in the 18th and 19th centuries were concerned with investment in education, posing the question: How do investments in education reflect in national wealth? And in increasing the possibility for greater profits of people as individuals! Although, even world-renowned economists have dealt with this issue, which based on empirical data provided explanations on the importance of mediation and economic growth.Considering that even developing and newest technological innovations derive from the process of educated individuals, it is very important to consider the impact of higher education on economic development.